Prenatal ultrasound diagnostics of atrioventricular communication in combination with the tetralogy of Fallot in a fetus with Down's syndrome phenotype - M.P. Veropotvelian; A.O. Bondarenko; О.V. Shashko; T.V. Usenko; D.I. Lailo (Publishing House TRILIST, 2022)
This article presents a description of our own case of ultrasound prenatal diagnostics of complex combined heart disease (complete atrioventricular communication in combination with tetralogy of Fallot) at 19-20 weeks of gestation with ultrasound markers of Down's syndrome in fetus. Pregnancy termination was performed at 21 weeks. Prenatal diagnosis was fully confirmed at the fetus autopsy. This publication discusses the frequency, mechanism of occurrence of such a combination of congenital heart defects, prenatal management, methods, timing and efficiency of surgical correction after birth. Complete atrioventricular communication occurs in approximately 1.7-2% patients with tetralogy of Fallot, and tetralogy of Fallot occurs in 5-10% of patients with atrioventricular communication, most often in patients with Down's syndrome. It is believed that tetralogy of Fallot and a complete defect of the atrioventricular septum develop as a result of different mechanisms, but their joint occurrence is recognized as an association. The prevalence of such a combination in Down syndrome indicates the general foundations of its development. Sonographic diagnosis of atrioventricular communication and tetralogy of Fallot is usually not difficult for prenatal screening. Main diagnostic criteria for complete atrioventricular communication at routine ultrasound screening and targeted fetal echocardiography are an abnormal 4-chamber image of the heart in the form of a common atrioventricular junction and a common five-leafed atrioventricular valve. Typical prenatal sonographic signs of the tetralogy of Fallot are a high defect of the interventricular septum, expansion of the aortic root, displacement of the aorta forward and to the right, narrowing of the pulmonary artery at the level of the valve ring from minor to complete atresia, it is also possible reduction the size of the right ventricle and increasing the size of the left ventricle. The combination of atrioventricular communication with the tetralogy of Fallot refers to severe congenital heart defects requiring surgical correction.